The Use of Interactive Game-Based Wordwall Media to Increase Student Participation in Pancasila Education - Sari, Yuli Ifana; Annisa, Ulfa Roudohtul; Sunaryati, Yenny (Actual Insight, 2025)
This research aims to increase the active participation of students in learning Pancasila and Citizenship Education through the use of interactive digital media Wordwall in class VIII-E State Junior High School 10 Malang. The background of this study is based on the results of initial observations that show low student participation during the learning process, where only about 40% of students are active in discussions and answering teachers' questions. The low participation is caused by the lack of variety of learning methods and media used, making students easily bored and tend to be passive. To overcome these problems, this study uses a qualitative descriptive approach with the Kemmis and McTaggart model class action research method which is carried out in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The research data was obtained through observation techniques of student participation during learning activities and questionnaires of student responses to the use of Wordwall media. The results showed a significant increase in student active participation from 40% at the pre-action to 68% at the end of the first cycle, and increased again to 85% at the end of the second cycle. In addition, students' enthusiasm and motivation to learn have also increased to reach 90%. These findings prove that the use of interactive digital media such as Wordwall is effective in creating a more participatory, fun, and motivating learning environment for students to be actively involved in Pancasila and Civic Education learning. Thus, the application of interactive media can be an alternative learning strategy that is relevant to improve the quality of the teaching and learning process in schools.